Forurettede i limbo - Ida Helene Asmussen; Louise Victoria Johansen; Lin Adrian; Lars Holmberg (Nordisk Tidsskrift for Kriminalvidenskab)
AbstractDuring the period 2018 to 2020, we followed 60 victims of crime and interviewed them at various stages of the judicial process from their first meeting with police until the conclusion of their cases. In this article, we analyze our interviews using Arnold Van Gennep’s and Victor W. Turner’s theoretical frameworks on rites de passage and social drama. Our analysis demonstrates how these theories are helpful in unravelling and deepening our understanding of victims’ experiences with the justice system.